Education for Peace in the Light of National Curriculum Framework â 2005 - Mondal, Ajit; Mete, Jayanta (EDUCARE, 2014)
ABSTRACT: We live in an age of unprecedented levels of violence, with constant threats posed by intolerance, fanaticism, dispute, and discordance. Ethical action, peace, and welfare are facing new challenges. A strong need is being felt by educationists, philosophers, scientists, and political leaders to rejuvenate the human values, which may bring long lasting peace on this planet. The purpose of education goes beyond the propagation of knowledge. J. Delorâs Report (1996) on learning to live together as the central pillar of education proposes that education must be geared to promote a culture of peace, tolerance, democratic values, human rights, and duties among students. With the reality of the alarming increase in violence in school life, the National Curriculum Framework (NCF) â 2005 strongly advocates education for peace at all levels of schools. In this backdrop, the present paper tries to epitomise the concept of education for peace in the light of NCF â 2005. Peace and living together have been integral part of Indian way of living and manifested in its Constitution through various articles. It firmly believes that inculcation of certain values among younger generation would help them to exist in the dynamic socio-cultural fabric with peace, harmony, and prosperity. In the final section, approach, strategies, activities, and teacherâs role in education for peace in the landscape of school education are also addressed as envisaged in the NCF â 2005.KEY WORDS: Education, peace, human values, harmony, tolerance, democracy, national curriculum framework, and Indiaâs government and society.Â Â About the Authors: Mr. Ajit Mondal and Dr. Jayanta Mete are a Research Scholar and an Associate Professor at the Department of Education, University of Kalyani, Kalyani, West Bengal, Pin-741235, India. The authors can be contacted via their e-mail at: mondalajit.edn@gmail.com and jayanta_135@yahoo.co.inHow to cite this article? Mondal, Ajit & Jayanta Mete. (2014). âEducation for Peace in the Light of National Curriculum Framework â 2005â in EDUCARE: International Journal for Educational Studies, Vol.6(2) February, pp.129-136. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 5, 2013); Revised (January 8, 2014); and Published (February 17, 2014).Â Â